THE INFLUENCE OF UNAVAILABILITY OF MEDICAMENTS AND LACK OF EMBARRASSMENT ON ONLINE PURCHASING OF MEDICAMENTS - Shukri, Shakeerah Mohd; Indang; Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
The current study aims to address this gap in existing research and attempts to offer a picture of specific determinants that significantly influence the customers’ perceived risk and trust during online shopping of medicaments. A theoretical model was also proposed to explain the influence of all of these encouraging and discouraging factors on the customers’ perceived risk and trust. In order to collect the data needed for the examination of this model, an online questionnaire was distributed, which resulted in 157 valid responses. The impacts of the variables of interest were further quantitatively evaluated by Principal Component Analysis (PCA), using SPSS as the statistical software. Therefore, the discouraging constructs were the most significant constructs affecting consumers’ intention to purchase medicaments online. The fact that the customers’ intention to purchase medicaments online is mostly controlled by discouraging factors may not necessarily be indicative of no potential for this purchase medium. The results of this research could assist online retailers in implementing appropriate strategies in decreasing the consumers’ perceived risk, thus increasing their online transactions.